2014
DOI: 10.1155/2014/961617
|View full text |Cite
|
Sign up to set email alerts
|

Isomers of Poly Aminophenol: Chemical Synthesis, Characterization, and Its Corrosion Protection Aspect on Mild Steel in 1 M HCl

Abstract: The oxidative chemical polymerizations of three isomers of aminophenol,ortho,meta, andpara(PoAP, PmAP, and PpAP), were performed in aqueous HCl using ammonium persulfate as an oxidant at 0–3°C. The synthesized polymers were characterized by employing elemental analysis, GPC, UV-VIS-NIR, FT-IR, XRD, and TGA. The corrosion inhibition effect of these three polymers on mild steel in 1 M HCl solution was studied by using electrochemical techniques such as potentiodynamic polarization and electrochemical impedance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…4-Aminophenol (4-AP) has been reported as a major product of 4-NP transformation in anaerobic environments (Gurevich et al, 1993) and polymerization of 4-AP is also known to occur (Thenmozhi et al, 2011(Thenmozhi et al, , 2014. We therefore hypothesized that the 4-NP loss was due to its reduction to 4-AP and/or its direct or indirect polymerization.…”
Section: Chemical Polymerization Of 4-aminophenolmentioning
confidence: 97%
See 2 more Smart Citations
“…4-Aminophenol (4-AP) has been reported as a major product of 4-NP transformation in anaerobic environments (Gurevich et al, 1993) and polymerization of 4-AP is also known to occur (Thenmozhi et al, 2011(Thenmozhi et al, , 2014. We therefore hypothesized that the 4-NP loss was due to its reduction to 4-AP and/or its direct or indirect polymerization.…”
Section: Chemical Polymerization Of 4-aminophenolmentioning
confidence: 97%
“…The diversity of compounds present in the synthetic sewage which is a complex medium (peptone, meat extract and urea) and the abundance of sulfate (26.3 ± 0.7 mg/L in the initial medium) could also favor this reaction. Furthermore, it has been shown that 4-AP can polymerize in presence of oxidizing agents such as hydrogen peroxide or ammonium persulfate (APS) (Duan et al, 2014;Thenmozhi et al, 2014). Thenmozhi et al (2014) observed the chemical synthesis of 4-AP in acidic conditions and Duan et al (2014) used horseradish peroxidase to catalyze 4-AP polymerization at pH 7 in the presence of hydrogen peroxide.…”
Section: Biodegradation Of 4-npmentioning
confidence: 99%
See 1 more Smart Citation
“…The product was then dried at 80 C for 12 h, and used for further process. 37 2.4.3. Synthesis of the poly aniline-poly para-aminophenol copolymer (PpAP-PANI).…”
Section: Conductive Polymer (Cp) Synthesismentioning
confidence: 99%
“…The product was dried at 80 C in vacuum oven, and stored for further process. 36,37 2.4.4. Synthesis of poly-pyrrole (pPy).…”
Section: Conductive Polymer (Cp) Synthesismentioning
confidence: 99%